Sumbangsih Pemikiran Kh. Hasim Asy’ari pada Kurikulum Pendidikan Pesantren (Telaah Kitab “Adabu al-Alim Waa al-Mutallim”) - Ashari, Hasim (MUNAQASYAH : Jurnal Ilmu Pendidikan dan Pembelajaran, 2020)
This article only focuses on the preliminary analysis of the book, the first, second, and third chapters. Meanwhile, the next chapters can be perfected by devotees, activists, and lovers of Hadratu as-Shaykh Kh Hasim Asy'ari in different writings and contexts. One of the famous and very influential figures in the land of Java is Hadratussyaikh KH Hasyim Asy'ari. He KH Hasyim Asy'ari has contributed to the development and growth of the Islamic world through monumental works, one of his books that became a reference is Adab Al-'Alim wal Muta'allim. The method used is qualitative with the type of library research. Qualitative research is natural research, examining real conditions that are not engineered at all. The conclusion is that the Book of Adab Al-'Alim wal Muta'allim animates the pesantren curriculum. The hope is that it can also animate the individuals of the students who are struggling to find knowledge. The book of Adab Al-'Alim wal Muta'allim is systematically constructed, the study begins with the introduction of the privileges of a scientist, arranging intentions when looking for knowledge, ethics of a scientist, and ethics in finding a teacher. The emphasis in Adab Al-'Alim wal Muta'allim is more on adab or character, this can be seen from Kh Hasim Asy'ari's quotes in verses, hadiths, and atsar of friends about the highest value of life.